Assessment of Social Vulnerability to the threat of fire in the Tomé-Açu Microregion (Research, Society and Development, 2022)
Recently, there have been many fires in Brazil, these strongly affecting the humid tropical forest. Several municipalities in Pará have had many fires and forest fires leaving serious consequences in the Amazon biome, increasing the vulnerability of the inhabitants of the most affected regions. Therefore, it is necessary to optimize risk prevention mechanisms and prepare communities to face possible disasters, training leaders for decision-making, raising their response capacities to build resilient communities. This study aimed to evaluate the social vulnerability of the Tomé-Açu Micro-region (MRTA) to the threat of fire. Geographic Information Systems (GIS) and ARCMAP 10.5 were used to prepare the maps; for multivariate statistical analyzes (K-Means clustering and PCA) R software, version 4.03 was used. A socio-environmental analysis was carried out considering demographic (demographic density and rural population), social (vulnerable by age group and level of education) and environmental variables (number of hotspots, rainfall, land use). The main results point to the municipality of Concórdia do Pará with high socio-environmental vulnerability to the threat of fire. With medium socio-environmental vulnerability appears Acará, whose environmental variables favor the reduction of this vulnerability, however, the social ones contribute negatively to the construction of this indicator. The other municipalities in the MRTA (Moju, Tailândia and Tomé-açu) have very similar environmental and social parameters and contributed to the construction of the indicator of low socio-environmental vulnerability to the threat of fire. This research reinforces the need to increase the education of this population to face possible disasters.